2021
DOI: 10.1111/dar.13292
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of alcohol dependence in an Australian Aboriginal and Torres Strait Islander representative sample: Using the Grog Survey App

Abstract: Introduction Little is known about the prevalence of current alcohol dependence in Indigenous Australian communities. Here we identify the frequency of reported symptoms, estimate the prevalence and describe the correlates of current alcohol dependence. Methods A representative sample of Indigenous Australians (16+ years) was recruited from an urban and remote community in South Australia. Data were collected between July and October 2019 via a tablet computer‐based application. Participants were likely depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is slightly lower than in a recent First Nations Australian community sample (2.2%; an urban and remote site). That study used an interactive iPad tool, validated among First Nations Australians, to ask three questions on dependence (derived from International Classification of Diseases, 11th Revision, features) [ 14 ]. Our prevalence of 1.6% is close to the 12‐month prevalence of 1.4% within the general Australian community (Diagnostic and Statistical Manual of Mental Disorders, fourth edition; diagnostic interview schedule) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is slightly lower than in a recent First Nations Australian community sample (2.2%; an urban and remote site). That study used an interactive iPad tool, validated among First Nations Australians, to ask three questions on dependence (derived from International Classification of Diseases, 11th Revision, features) [ 14 ]. Our prevalence of 1.6% is close to the 12‐month prevalence of 1.4% within the general Australian community (Diagnostic and Statistical Manual of Mental Disorders, fourth edition; diagnostic interview schedule) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterised by a strong internal compulsion to consume alcohol with impaired ability to control one's use. Among First Nations Australians, the prevalence of alcohol dependence is similar to that of the general Australian population (2.2% vs. 1.4%, aged 16+) [14, 15]. Harms to individuals, their families and communities can be greater in dependence [9].…”
Section: Introductionmentioning
confidence: 99%
“…Communities could use the App for this ongoing monitoring. In addition to estimating the proportion of people at long‐ and short‐ term risk, the App monitors prevalence of alcohol dependence 22 . Beyond identifying whether a community needs support, the App can also help identify which population subgroups within communities are most at risk.…”
Section: Monitoring and Responding To Risky Drinking And Dependence W...mentioning
confidence: 99%
“…Beyond identifying whether a community needs support, the App can also help identify which population subgroups within communities are most at risk. For example, using data collected with the App, in one community we found that men and those with lower incomes were more likely to be dependent on alcohol 22 . This information could be used to establish support groups for men, so they can connect with others and ensure their basic psychological needs are satisfied in safe ways 23 …”
Section: Monitoring and Responding To Risky Drinking And Dependence W...mentioning
confidence: 99%
“…Alcohol contributes to 8.1% of the health gap between First Nations Australians and other Australians [ 4 ]. This is despite the fact that more Aboriginal and Torres Strait Islander peoples than non-Indigenous are current non-drinkers [ 5 ], and prevalence of dependence (2.2%) is similar to the general population [ 6 ]. However, when First Nations Australians people do drink, they consume a median of 78 g of alcohol per occasion, well over the Australian recommended limit to reduce risk of short-term harms, like injury, from alcohol (40 g per occasion) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%